Prognostic Significance of Lactate Dehydrogenase for in Hospital Mortality in Intensive Care Units with Covid-19 in Tertiary Care Level Hospital in Northern Pakistan - Haroon Ur Rasheed, Hayat Muhammad Khan, Mohsin Shafi, Naeemullah, Saeed Ahmad, Romana Ayub, Arif Iqbal, Muhammad Ishtiaq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Lactate dehydrogenase was found as the prognostic indicator of poor outcomes and severity of COVID-19. In many studies, COVID-19 patients with different LDH showed relationship with disease progression and mortality. Objectives: To determine prognostic significance of Lactate dehydrogenase (LDH) in critically ill patients with Covid-19 infection. Material & Methods: A retrospective descriptive cross sectional study was conducted among the Covid-19 ICU admitted patients of Khyber Teaching Hospital Peshawar. Moreover, data regarding n=233 COVID-19 serious infection, confirmed on Polymerase chain reaction (PCR), was analyzed. Prognostic significance of LDH was determined by using SPSS software. Results: Compared to the survival group, LDH levels among the Covid-19 mortality individuals were significantly higher. A cutoff value of 330 U/L was set for the test results determined spectro-photometrically by chemistry analyzer. Chi-Square test value was 17.23 with P value of 0.004. Conclusion: LDH is one of the cheap and significant prognostic parameter and is beneficial in forecasting hospital death in severely ill COVID-19 patients; may assist doctors focus on saving the lives of their highest-risk patients and apply new measures to lower mortality rates.. Keywords: Lactate Dehydrogenase, Prognostic Value, Mortality, Intense Care Unit, COVID-19